Studies in the genus Riccia (Marchantiales) from southern Africa. 18. New species in section Pilifer from the NW Cape: R. furfuracea, R. vitrea and R. namaquensis - S. M. Perold (Bothalia: African Biodiversity & Conservation, 1990)
Another three new species of Riccia in section  Pilifer Volk are described from Namaqualand, namely  R. furfuracea, R vitrea and R. namaquensis. There are certainly more undescribed species present in that region, but species from there are often very difficult to distinguish: almost all have hyaline scales, the free-standing dorsal cell pillars need to be examined in living plants and the spore ornamentation is quite variable.